Alcohol and epigenetic changes: Summary of the 2011 Alcohol and Immunology Research Interest Group (AIRIG) meeting - Zahs, Anita (2012)
On November 18, 2011, the 16th annual Alcohol and Immunology Research Interest Group (AIRIG) meeting was held at Loyola University Medical Center in Maywood, Illinois. The focus of this year’s meeting was alcohol’s effect on epigenetic changes and possible outcomes induced by these changes. Two sessions, which consisted of talks from invited speakers as well as presentations of selected abstracts, were held in addition to a poster session. Participants presented information on alcohol-induced alterations in histone modifications and gene expression along with immunologic responses to alcohol. Speakers shared new research specifically on histone deacetylase enzyme expression and modifications due to alcohol and the downstream effect of these modifications may have on gene expression and tissue damage. Additional studies suggested that alcohol exacerbates inflammation when combined with other insults such as infection, trauma, inhalation injury, and disease.